Application of a Sensitive Capture Sequencing Approach to Reservoir Surveillance Detects Novel Viruses in Zambian Wild Rodents - Moonga, Lavel C.; Chipinga, Jones; Collins, John P.; Kapoor, Vishal; Saasa, Ngonda; Nalubamba, King S.; Hang’ombe, Bernard M.; Namangala, Boniface; Lundu, Tapiwa; Lu, Xiang-Jun; Yingst, Samuel; Wickiser, J. Kenneth; et al. (Viruses, 2024)
We utilized a pan-viral capture sequencing assay, VirCapSeq-VERT, to assess viral diversity in rodents from the Eastern Province of Zambia as a model for pre-pandemic viral reservoir surveillance. We report rodent adeno-, parvo-, paramyxo-, and picornaviruses that represent novel species or isolates, including murine adenovirus 4, two additional species in the genus Chaphamaparvovirus, two paramyxoviruses distantly related to unclassified viruses in the genus Jeilongvirus, and the first Aichivirus A sequence identified from rodents in Africa. Our results emphasize the importance of rodents as a reservoir for potential zoonotic viruses.